Fluorescence Imaging Analysis of Upstream Regulators and Downstream Targets of STAT3 in Melanoma Precursor Lesions Obtained from Patients Before and After Systemic Low-Dose Interferon-α Treatment - Amanda Pfaff Smith; John M. Kirkwood; Howard D. Edington; Drazen M. Jukic; Daniel L. Farkas; Dorothea Becker (Molecular Imaging)
Atypical nevi are the precursors and risk markers of melanoma. Apart from persistently monitoring these nevocytic lesions and resecting them at the earliest signs of clinical changes, there is as yet no systemic clinical treatment available to interfere with their progression to melanoma. To explore clinical treatments that might interfere with and possibly prevent atypical nevus progression, a previous study documented that 3 months systemic low-dose interferon-α (IFN-α) treatment of patients with a clinical history of melanoma and numerous atypical nevi, led to inactivation of the STAT1 and STAT3 transcription factors in atypical nevi. Based upon this finding, we initiated a second study to determine whether systemic low-dose IFN-α treatment also impairs the expression of upstream regulators and downstream targets of STAT1 and STAT3 in atypical nevi. Using cyanine dye-conjugated antibodies, fluorescence imaging analysis revealed expression of JAK2, JNK1, AKT1, NF-κB, and IFN-αβ receptor in benign and atypical nevi, and early- and advanced-stage melanomas. To determine possible changes in the level of expression of these molecules in atypical nevi, excised before and after 3 months of systemic low-dose IFN-α treatment, newly designed optical imaging software was used to quantitate the captured fluorescent hybridization signals on a cell-by-cell basis and across an entire nevus section. The results of this analysis did not provide evidence that systemic low-dose IFN-α treatment alters the level of expression of upstream regulators or downstream targets of STAT1 and STAT3.